Root growth responses to water and nitrogen inputs drive maize economic income and water-nitrogen productivity - Bo Jing; Wenjuan Shi (Agricultural Water Management)
Low water and nitrogen use efficiency in Northwest China constrains maize profitability, highlighting the need to optimize their management to enhance soil resource utilization for sustainable production. To investigate the effects of water and nitrogen management on maize economic income, root growth, and water-nitrogen productivity, a two-year field experiment was conducted in Northwest China using a two-factor randomized complete block design. The treatments comprised three irrigation amounts [60 % (W1), 80 % (W2), and 100 % of the crop potential evapotranspiration (W3)] and five nitrogen application rates [0 (N0), 80 (N1), 160 (N2), 240 (N3), and 320 kg ha–1 (N4)]. The results showed that the combination of W2 (economic income increased by 2.06–38.84 %) and N3 (economic income increased by 7.12–76.95 %) achieved the highest crop and water productivity among all irrigation and nitrogen treatments. Meanwhile, the highest nitrogen partial factor productivity was observed under W3 and N1. Maize root growth followed a ''beta'' model, with optimal root parameters under W3 and N3, and enhanced economic income and water productivity were linked to root development in the 40–80 cm layer. The optimal irrigation range (345–364 mm) and nitrogen application range (160–319 kg ha–1) were determined based on economic income and water productivity, ensuring the conditions for achieving up to 95 % of the maximum values. These findings underscore the central role of root growth responses in mediating the effects of water and nitrogen inputs.